REKAYASA SASTRA SEBAGAI UPAYA MENINGKATKAN GERAKAN LITERASI DI KALANGAN GENERASI MUDA - Ninawati syahrul (Balai Bahasa Sulawesi Tengah, 2019)
Characteristics of quality literary works must carry and convey moral messages. As a civilized citizen, the young generation — of course other citizens — must seize moral values in treading diverse lives. In this regard, literary engineering is an idea that should be taken into account as a form of literary approach in accordance with the mental development of the younger generation. How far is literary engineering capable as a new idea to introduce literature to the younger generation, that is the problem in this paper? This paper aims to describe and